Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Cover Image - Chia‐Yu Hsieh; Shang‐Ting Wu; Chun‐Ying Lin (Journal of Fish Diseases, 2026)

Safety evaluation and probiotic properties of Bacillus velezensis YK-19 capable of degrading deoxynivalenol: In vitro characterization and in vivo safety assessment in mice - Yukai Lin; Jingjing Zhao; Bo Wen; Songbiao Chen; Lei Wang; Xiaojing Xia; Yanzhao Xu; Yanyan Jia; Rongxian Guo; Ke Shang; Zuhua Yu; Chengshui Liao; et al. (Food Bioscience, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Intelligent monitoring and management of urban drainage systems through machine-learning-driven fusion of EEM and UV-Vis - Hao-Lin Yang; Xin Zhang; Shang-Wen Deng; Jia-Min Xu; Ruo-Zhou Lin; Zhi-Yu Zhang; Yu-Qi Wang; Ding-Ding Tang; Hong-Cheng Wang (Journal of Environmental Management, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Isolation and Identification of Erysipelothrix sp. in Hybrid Grouper ( Epinephelus fuscoguttatus × E. lanceolatus ) in Taiwan - Shang‐Ting Wu; Yu‐Siang Lin; Chia‐Yu Hsieh (Journal of Fish Diseases, 2026)
In February 2025, a mortality event of unknown aetiology occurred at a hybrid grouper ( Epinephelus fuscoguttatus × Epinephelus lanceolatus ) aquaculture farm in southern Taiwan, with sporadic daily deaths persisting for a month. Four moribund groupers were collected over three sampling intervals for diagnostic investigation. Gross pathology revealed opaque white discoloration with multifocal petechial haemorrhages in the lateral musculature. Gram‐stained muscular viscous fluid smears showed abundant Gram‐positive, filamentous bacilli (2–100 μm in length). Histopathology of the skeletal muscle confirmed extensive Zenker's necrosis, with dense bacterial aggregates infiltrating necrotic myofibres. On blood agar at 28°C, smooth, greyish, α‐haemolytic colonies developed within 16–24 h; growth was restricted at 32°C and absent at 35°C. Full‐length 16S rRNA gene sequencing identified the isolates as Erysipelothrix . High‐resolution gyrB ‐based phylogenetic analysis clustered the isolates nearly identically with the dolphin‐derived E. rhusiopathiae strain KC‐Sb‐R1 (CP033601), distinct from swine‐derived E. rhusiopathiae (97.0%), E. piscisicarius (91.2%) and E. tonsillarum (83.9%). The isolates belonged to spa type B. To our knowledge, this is the first documented case of an E. rhusiopathiae ‐like infection causing myositis and intramuscular abscesses in grouper aquaculture, highlighting a potentially marine‐associated lineage with significant implications for aquatic veterinary medicine and public health.

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Constructed wetland assessment using BC-CaCO3/TiO2 biochar in acid mine drainage treatment: Performance and metagenomic insights - Thembeka Mabaso; Shang-Lien Lo; Hsiang-Yu Yang; Nai-Chun Lin (Journal of Environmental Chemical Engineering, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

In Situ Hybridization and RT ‐ PCR Detection of Nervous Necrosis Virus in Fourfinger Threadfin, Eleutheronema tetradactylum , in Taiwan - Chia‐Yu Hsieh; Shang‐Ting Wu; Chun‐Ying Lin (Journal of Fish Diseases, 2026)
Between April and July 2020, suspected outbreaks of nervous necrosis virus (NNV) infection were observed in fourfinger threadfin ( Eleutheronema tetradactylum ) fingerling hatcheries in Pingtung County, southern Taiwan. Affected fish exhibited spiral swimming behaviour and abdominal distension, resulting in mortality rates between 50% and 100%. Histopathological examination showed severe vacuolation in the brain and ocular tissues, with large oval and/or irregular basophilic cytoplasmic inclusion bodies in the brain. Phylogenetic analysis of the viral replicase (RNA1) and capsid protein (RNA2) genes revealed high nucleotide sequence identities among the isolates in this study, with sequence similarity rates of 96.9%–99% for RNA1 and 98.2%–99.0% for RNA2 compared to RGNNV reference strains available in the NCBI GenBank database. This is the first detection of betanodavirus in fourfinger threadfin in Taiwan, using RT‐PCR and ISH. A positive correlation between elevated water temperatures and disease severity indicates the need for year‐round surveillance and genomic analysis to clarify the epidemiology of FTNNV. The data suggest that infected eggs may facilitate the vertical transmission of Betanodavirus. Crucially, utilising virus‐free broodstock, alongside routine health screening and environmental control, is essential for mitigating NNV risks in fourfinger threadfin aquaculture.

A stimulating effect induced by Bisphenol A bis (diphenylphosphate) in HepG2 cells via vascular endothelial growth factor (VEGF)/VEGF receptor axis - Jing An; Yuting Yi; Na Li; Miao Lin; Yufang Zhong; Guofa Ren; Yu Shang (Toxicology Letters, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Physicochemical properties on the bone of hairtail (Trichiurus lepturus) under various treatments of cooking pressure and vinegar - Huey-Jine Chai; Shang-Ta Wang; Yun-En Chung; Yi-Ting Pan; Yu-Cheng Lin; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Whitening and antioxidant activities of Inonotus sanghuang Extract and development of primary whitening gel products - Liang Zhang; Hui-Lin Zhao; Shang-De Peng; Sempere Deguol Mawunya; Yao Zhang; Hai-Chen Li; Yu Luo; Yan Wen (Natural Product Research, 2025)

Quantifying mutual transport contributions of ozone and its precursors among adjacent county-level cities during typical pollution episodes - Demian Lai; Yifei Chen; Yangjun Wang; Yan Zhang; Lin Xu; Zijia Ma; Burcak Kaynak; Shikang Tao; Yu Shang; Li Li (Urban Climate, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Extraction of Chlorella polysaccharide using natural deep eutectic solvent - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Huiqing Zhang; Changhua Shang (Algal Research, 2025)

The methods for the retrieval of land surface temperature in central Shijiazhuang using ASTER data - Biao Zeng; Guo-fei Shang; Xia Zhang; Ye-lin Shen; Yu-jia Tian; Zheng-hong Yan (Environmental Monitoring and Assessment, 2025)

Extraction, purification and antioxidant activity of Chlorella polysaccharide - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Changhua Shang (Algal Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Extraction, purification and characterization of Spirulina phycocyanin - Juying Lin; Yan Pang; Yu Huo; Jiaming Jiang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

A novel physics-based cloud retrieval algorithm based on neural networks (CRANN) from hyperspectral measurements in the O2-O2 band - Wenwu Wang; Husi Letu; Huazhe Shang; Jian Xu; Huanhuan Yan; Lianru Gao; Chao Yu; Jianbin Gu; Jinhua Tao; Na Xu; Lin Chen; Liangfu Chen (Remote Sensing of Environment, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Influence of cyclic hardening characteristic on seismic performance of welded austenitic stainless steel H-section beam-column - Yu Chen; Feng Zhou; Shuai Zheng; Jianquan Li; Chengzhi Shang; Xingxin Lin (Engineering Structures, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Transcriptomic and metabolomic analyses revealed epiboly delayed mechanisms of 2,5-dichloro-1, 4-benuinone on zebrafish embryos - Yuanyao Chen; Jingming Wang; Zhiquan Yu; Lin Xiao; Jia Xu; Kai Zhao; Huiping Zhang; Xuejun Shang; Chunyan Liu (Environmental Science and Pollution Research, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Impact of Petroleum Contamination on the Structure of Saline Soil Bacterial Communities - Ying Zhang; Xiaojie Sun; Cheng Qian; Lin Li; Xiufang Shang; Xinfeng Xiao; Yu Gao (Current Microbiology, 2022)

Role of ocean dynamics in equatorial Pacific decadal variability - Yu Zhang; Shi-Yun Yu; Shang-Ping Xie; Dillon J. Amaya; Qihua Peng; Yu Kosaka; Xiaopei Lin; Jun-Chao Yang; Sarah M. Larson; Arthur J. Miller; Lei Fan (Climate Dynamics, 2022)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Spatial variation and association between maternal chemical fertilizer exposure and preterm birth in a rural area in Northern China - Jiajia Li; Shiqi Lin; Jilei Wu; Yu Li; Xuejun Shang; Lijun Pei (Environmental Science and Pollution Research, 2022)

Effects of periodically varying codes on separation of multisource blended data - Meng-Yao Jiao; Tian-Yue Hu; Yang Liu; Zhen-Zhen Yu; Shang-Lin Liang; Li-Chao Liu; Ji-Wei (Applied Geophysics, 2021)

Description of the reservoir along strike-slip fault zones in China T-Sh oilfield, Tarim Basin - Rui Zhao; Shang Deng; Lu Yun; Huixi Lin; Teng Zhao; Chen Yu; Qiangfu Kong; Qiang Wang; Huili Li (Carbonates and Evaporites, 2021)

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Uncertainty of volume fraction in bimrock using the scan-line method and its application in the estimation of deformability parameters - Yu-Chen Lu; Yong-Ming Tien; Charng Hsein Juang; Jeen-Shang Lin (Bulletin of Engineering Geology and the Environment, 2020)
The volume fraction within a bimrock or bimsoil is an essential parameter that is useful for estimating the engineering properties of heterogeneous geomaterials. This paper presents analytical and numerical solutions to quantify the uncertainty of volume fraction measurements in bimrock/bimsoil using a scan-line method. The analytical solutions for the mean and variance of volume fraction estimates are based on a representative volume element model. The numerical solution is obtained through simulations of scan-line measurements. This work also employs physical tests using CT scan images from artificial bimrock/bimsoil to validate these solutions. The results demonstrate that the uncertainties of the volume fraction depend on the magnitude of the volume fraction of the blocks, the diameter of the blocks, and the length of the scan line. The proposed analytical and numerical solutions are compared with existing physical experimental tests and analytical solutions. An illustrative example to demonstrate the estimation of the uncertainty of volume fraction using the scan-line measurement is present. Finally, an example application of the volume fraction characterization in the geological engineering, in terms of Young’s modulus estimation and characterization, is provided.

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Autoinducer-2 signaling is involved in regulation of stress-related genes of Deinococcus radiodurans - Lin Lin; Tao Li; Shang Dai; Jiangliu Yu; Xiuqin Chen; Liangyan Wang; Yunguang Wang; Yuejin Hua; Bing Tian (Archives of Microbiology, 2016)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Mechanism-Based Pharmacokinetic/Pharmacodynamic Model for THIOMAB™ Drug Conjugates - Siddharth Sukumaran; Kapil Gadkar; Crystal Zhang; Sunil Bhakta; Luna Liu; Keyang Xu; Helga Raab; Shang-Fan Yu; Elaine Mai; Aimee Fourie-O’Donohue; Katherine R. Kozak; Saroja Ramanujan; et al. (Pharmaceutical Research, 2015)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Phosphorus Load Reduction Goals for Feitsui Reservoir Watershed, Taiwan - Wen-Shang Chou; Tsu-Chuan Lee; Jen-Yang Lin; Shaw L. Yu (Environmental Monitoring and Assessment, 2007)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Cloning and expression of the α-amylase gene and oxytetracycline production in Streptomyces rimosus - Chun-Wen Cheng; Jin-Seng Lin; Yu-Tien Liu; Shang-Shyng Yang (World Journal of Microbiology and Biotechnology, 2000)